Training on Authentic Assessment Preparation to Improve Teacher Professional on Junior High School Science in Bengkulu City - Medriati, Rosane; Purwanto, Andik; Kashardi, Kashardi; Putri , Desy Hanisa; Mantili, Lenni (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2023)
The background to this Community Service is the difficulty of teachers in designing and implementing assessments, Authentic Assessments and carrying out learning evaluations well. Therefore, a form of socialization and workshops regarding the development of authentic evaluation and assessment is needed to provide skills to teachers in creating science learning tools that are effective in developing authentic assessments in accordance with the 2013 curriculum. The service method is carried out through pre-surveys, literature review, outreach, and workshops. The strategic target audience for this authentic assessment preparation training is science teachers at Public Junior High School No. 11 Bengkulu City (SMP Negeri 11 Bengkulu City). The location for the socialization and workshop is the Laboratory of SMP Negeri 11 Bengkulu City. The results of community service in the form of training and preparation of authentic assessments in accordance with the 2013 curriculum for science teachers at Public SMP No 11 Bengkulu City which have been implemented (1) can improve teachers' abilities to design authentic assessments in accordance with the 2013 curriculum so that teachers can improve their teaching abilities professionally. (2) Teachers can create effective science learning tools and are able to develop authentic assessments that must be in accordance with what has been outlined in Minister of Education and Culture Regulation No. 23 of 2016 so that teachers can implement the tools in the classroom efficiently.